A new framework for the design and analysis of identity-based identification schemes - YANG, Guomin (Institutional Knowledge at Singapore Management University, 2008)
Constructing an identification scheme is one of the fundamental problems in cryptography, and is very useful in practice. An identity-based identification (IBI) scheme allows a prover to identify himself to a public verifier who knows only the claimed identity of the prover and some public information. In this paper, we propose a new framework for both the design and analysis of IBI schemes. Our approach works in an engineering way. We first identify an IBI scheme as the composition of two building blocks, and then show that, with different security properties of these building blocks, the corresponding IBI schemes can achieve security against impersonation under different levels of attacks, namely, passive attack (id-imp-pa), active attack (id-imp-aa) or concurrent attack (id-imp-ca). In particular, we show that an id-imp-pa secure IBI scheme can be built if there exists a trapdoor weak-one-more relation and an honest verifier zero-knowledge proof with special soundness, while an id-imp-aa and id-imp-ca secure IBI scheme can be built if there exists a trapdoor strong-one-more relation and a Witness Dualism proof with Special Soundness (WD-SS). This new framework can capture IBI construction techniques that are not captured by other known frameworks. It also helps to construct new and efficient schemes. We demonstrate this by proposing two new IBI schemes, one achieving id-imp-pa, and the other one achieving both id-imp-aa and id-imp-ca, and neither of them can be captured by existing frameworks.